Technical Competence of Group Leaders, Managerial Role, and Productivity in Engineering Design Groups - Slusher, Allen; Dyke, James Van; Rose, Gerald L. (Academy of Management Journal, 1972)
This study focuses on nine group leaders of matched engineering design groups. A significant negative correlation was found between the group leaders' technical competence and their managerial role adoption. A strong positive correlation between managerial role adoption and group productivity was obtained. It is suggested that engineers with high technical competence tend to reject the role of manager.